Gestão temerária de fundos de pensão - Zanetti, Adriana Freisleben de (2017)
Closed private pension entities, in Brazil also known as “pension funds”, integrate the voluntary complementary private pension system. Unlike opened entities, that operate based on profit objective, closed private pensions entities are prohibited by law to obtain profits. In this way, closed private pension entities are assets directly linked to the scope of paying the contracted social security benefits. To correctly reach their scope, closed private pension entities must be well managed. Risks related to assets and liabilities should be taken account into, by elaborating the entity’s actuarial and financial premises and goals. Risk is a key point to be considered, especially after the dimension it has taken in the risk society. The asset and liability management model to be adopted by closed private pension entities must be based on practices that reduce the risks that pension funds face, with the aim of diminishing correlated threats that could lead to entity’s crash. Reckless management in pension funds occurs when entities’ administrators act unwary of prudent person rule standards and are heedless of the conservative measures destined to maintain the balance between the entities’ assets and liabilities. However, the concept of reckless management in pension funds cannot be established a priori, since it depends on further legal statutes integration to judge the entities’ administrators deportment as contrary to the rule of law